2018
DOI: 10.21107/infestasi.v13i2.3514
|View full text |Cite
|
Sign up to set email alerts
|

Tax Compliance Ditinjau dari Theory of Planned Behavior (TPB): Studi Empiris Pada Wajip Pajak Orang Pribadi dan Badan yang Terdaftar Pada KPP di Kota Palembang

Abstract: <p>This study aims to analyze the factors that affect the tax compliance by <br />using Theory of Planned Behavior Approach (TPB). This study used survey design with data collection techniques by using questionnaires, where the selected respondents are taxpayers of individuals and entities registered at the KPP in the city of Palembang. The results showed that the variables that influence the intention to abide positively are the control behavioral variable and moral obligation, while the variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 0 publications
6
11
0
16
Order By: Relevance
“…Overall, this result supports the previous studies executed by Alpriyamah and Adityawarman (2017) that found the attitude and subjective norm toward behavioral intention to pay zakat were significant; Lesmana, Panjaitan, and Maimunah (2017) that concluded in terms of tax compliance, the variables that affecting positively the intention to pay were the control behavioral; Saad and Haniffa (2014) that found intention was significant predictor for zakat compliance behavior, intention was proved to be influenced by attitude and subjective norm.…”
Section: The Fourth Hypothesis: There Is Influence From Behavioralsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, this result supports the previous studies executed by Alpriyamah and Adityawarman (2017) that found the attitude and subjective norm toward behavioral intention to pay zakat were significant; Lesmana, Panjaitan, and Maimunah (2017) that concluded in terms of tax compliance, the variables that affecting positively the intention to pay were the control behavioral; Saad and Haniffa (2014) that found intention was significant predictor for zakat compliance behavior, intention was proved to be influenced by attitude and subjective norm.…”
Section: The Fourth Hypothesis: There Is Influence From Behavioralsupporting
confidence: 88%
“…Moreover, they found that intention to pay zakat was positively significant toward zakat compliance behavior. Lesmana, Panjaitan, and Maimunah (2017) also concluded that in terms of tax compliance, the variables that affecting positively the intention to pay were the control behavioral and moral obligation, while the attitude and subjective norms did not influence it. Yusuf and Ismail (2017) also proved that there was a significant impact of knowledge in taxation and zakat on taxpayers' compliance in paying tax.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Lesmana et al (2017) Kepatuhan wajib pajak ialah kondisi wajib pajak untuk melakukan hak dan kewajibannya, dengan taat sesuai aturan pajak yang berlaku. Kepatuhan ini diartikan bagaimana menyampaikan keseluruhan informasi yang dibutuhkan dengan tepat waktu, mengisi dengan benar beban pajak , dan menunaikan pajak tepat waktunya.…”
Section: Kajian Teori Kepatuhan Wajib Pajakunclassified
“…Sikap taat maupun tidak taat wajib pajak untuk melaksanakan pajakanya dipengaruhi niat yang dipunyai wajib pajak. Jika wajib pajak mempunyai niat dalam taat terhadap kewajibannya maka timbulah sikap kepatuhan pajak(Lesmana et al 2017).Menurut Riadita dan Suryadi (2018) kepatuhan wajib pajak bisa diartikan seperti kondisi wajib pajak melaksanakan seluruh kewajiban pajak dan mengerjakan hak pajaknya. Kepatuhan Wajib Pajak bisa diakibatkan beberapa faktor, faktor eksternal ataupun faktor internal.…”
unclassified
“…Thus, this system automatically relies on the volunteerism of the taxpayer in making payments (Sari & Susanti, 2015). A behavioral theory often used to describe taxpayer compliance is the TheoryTheory of planned behavior (TPB) (Lesmana et al, 2018). This TheoryTheory explains that a person's behavior will be formed with the intention, affecting the perceived attitudes, norms, and behavioral control (Lesmana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%